뇌사의 법적 측면 - 주호노(Ho-No Joo) (생명, 윤리와 정책, 2019)
이 논문은 법률상 법률효과를 달리하는 사람과 사체의 경계선으로서의 사람의 종기에 관하여 고찰하고 있다. 이 논문은 현행법상 사망의 판정 기준을 전통적으로 인정되어 온 심장사와 장기이식에 제한된 범위에서 새롭게 등장한 뇌사로 파악하고 있다. 나아가 이 논문은 의학기술의 비약적 발달로 인하여 사망의 판정방법에 있어서 심장사와 함께 뇌사의이원화가 도모되고 있을 뿐만 아니라 심장사에 있어서도 새로운 판정방법으로서의 심장사후기증(donation after cardiac death, 이하 DCD)의 도입이 요청됨으로써 사망 판정방법에 있어서의 의료화의 방법이 과제로 남게 되었다고 진단하고 있다. 끝으로 이 논문은 결어로서 규범적 평가에 있어서 자연사와의 동등성, 즉 DCD 또는 뇌사가 심장사와 같이 생명의 종국적이고 불가역적 소멸이라는 의학적 평가의 정확성과 일반인에 의한 사회적 수용의 당연성이라는 요건의 충족을 전제로 DCD의 도입 가능성과 뇌사의 독자성을 긍정하고 있다. This paper examines the end of human life as a boundary between living person and dead body that differs in legal effects. Under the current law, this paper considers a traditionally accepted cardiac death and a newly emerged brain death from a limited range of organ transplantation as a criteria of death determination. In addition, this paper diagnoses that the method of medicalization in death determination criteria remains a future problem not only due to needs of dualization of cardiac death and brain death in criteria of death determination but also due to introduction of donation after cardiac death in criteria of cardiac death determination based on the rapid development of medical technology. Finally, this paper concludes that the accept possibility of donation after cardiac death and brain death as criteria of cardiac death determination and death determination depends on the equivalence with natural death in normative evaluation, that is satisfaction of conditions such as the accuracy of the medical determination about ultimate irreversible extinction of life and the logic of the social acceptance by the general public. KCI Citation Count: 2